The transformative power embedded in Δεῦτε ὀπίσω μου and Ἀκολούθει μοι in Matthew as gospel embodiment in contemporary ecclesial discipleship - Botha, Roedolf (HTS teologiese studies, 2021)
Are churches missing some key aspects of discipleship? Are churches missing a primary way in which Jesus ushered people into a journey of personal renewal? I think that it is clearly the case, and that the transformative power that ecclesial communities seek is to be found in Jesus’ invitations to follow. Jesus invited people in his day to ‘Follow Me’ (Δεῦτε ὀπίσω μου or Ἀκολούθει μοι).Contribution: Implicit in these invitations are ideas like embodiment and movement, ideas that are vital in leading to deep and authentic personal as well as communal, transformation.